Antagonistic interactions between two MAP kinase cascades in plant development and immune signaling. (22nd May 2018) - Sun, Tongjun; Nitta, Yukino; Zhang, Qian; Wu, Di; Tian, Hainan; Lee, Jin Suk; Zhang, Yuelin
Abstract: Mitogen‐activated protein kinase (MAPK) signaling plays important roles in diverse biological processes. In Arabidopsis, MPK3/MPK6, MKK4/MKK5, and the MAPKKK YODA (YDA) form a MAPK pathway that negatively regulates stomatal development. Brassinosteroid (BR) stimulates this pathway to inhibit stomata production. In addition, MPK3/MPK6 and MKK4/MKK5 also serve as critical signaling components in plant immunity. Here, we report that MAPKKK3/MAPKKK5 form a kinase cascade with MKK4/MKK5 and MPK3/MPK6 to transduce defense signals downstream of multiple plant receptor kinases. Loss of MAPKKK3/MAPKKK5 leads to reduced activation of MPK3/MPK6 in response to different pathogen‐associated molecular patterns (PAMPs) and increased susceptibility to pathogens. Surprisingly, developmental defects caused by silencing of YDA are suppressed in the mapkkk3 mapkkk5 double mutant. On the other hand, loss of YDA or blocking BR signaling leads to increased PAMP‐induced activation of MPK3/MPK6. These results reveal antagonistic interactions between a developmental MAPK pathway and an immune signaling MAPK pathway. Synopsis: MAPKKK3/5 act upstream of MKK4/5 and MPK3/6 in PAMP‐triggered and DAMP‐triggered immunity in plants. The MAPK pathways specified by MAPKKK3/5 and the developmental YDA pathway antagonize by competing for downstream MKKs. MAPKKK3/5, MKK4/5 and MPK3/6 form a MAPK cascade to transduce defence signals in PTI. Developmental defects caused by silencing YDA are suppressed in the mapkkk3/5 double mutant. Loss of YDA leads to increased PAMP‐induced activation of MPK3/MPK6. Brassinosteroid has an inhibitory effect on PAMP‐induced MAPK activation. Abstract : MAPKKK3/5 act upstream of MKK4/5 and MPK3/6 in PAMP‐triggered and DAMP‐triggered immunity in plants. The MAPK pathways specified by MAPKKK3/5 and the developmental YDA pathway antagonize by competing for downstream MKKs.